2011
DOI: 10.1016/j.jss.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of COX-2 in Tumorospheres Derived from a Breast Cancer Cell Line

Abstract: Background-Cyclooxygenase-2 (COX-2) expression in primary breast cancer predicts tumor cell dissemination to bone marrow, which is a risk factor for recurrence and distant metastasis. "Stem-like" phenotype may be important in cancer metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 37 publications
4
40
1
Order By: Relevance
“…According to the ICC assay, COX-2 expression was reduced significantly in MCF-7 cells, with no reduction in their CSC-LCs. It has also been observed that celecoxib, at 10 µM, dramatically suppressed the tumorsphere and colony-forming capacity of MCF-7 cells, which is a hallmark of CSCs in vitro (Singh et al, 2011). It was recently demonstrated that celecoxib can effectively harness MDR-1 expression in the doxorubicinresistant MCF-7 cell line, which is mediated by inhibiting AP-1 and NF-κB transcription factors, suggesting the use of a selective COX-2 inhibitor in combination therapy as a promising avenue for successful breast cancer treatment (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…According to the ICC assay, COX-2 expression was reduced significantly in MCF-7 cells, with no reduction in their CSC-LCs. It has also been observed that celecoxib, at 10 µM, dramatically suppressed the tumorsphere and colony-forming capacity of MCF-7 cells, which is a hallmark of CSCs in vitro (Singh et al, 2011). It was recently demonstrated that celecoxib can effectively harness MDR-1 expression in the doxorubicinresistant MCF-7 cell line, which is mediated by inhibiting AP-1 and NF-κB transcription factors, suggesting the use of a selective COX-2 inhibitor in combination therapy as a promising avenue for successful breast cancer treatment (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…COX-2 expression has been implicated in CSC proliferation and CSC-assisted metastasis [45,56,57]. As 3 possesses two tolfenamic acid molecules, which are well-known COX-2 inhibitors, flow cytometric studies were conducted to determine if the mechanism of action of 3 involved COX-2 inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…[137][138][139][140][141] In murine models of breast cancer, COX-2 has been shown to be involved in osteoclastogenesis (via IL-11) [138] and stimulation of osteoclasts to resorb bone (via PGE2 and IL-8). [139] It has also been associated with increased tumourgenicity and clonogenicity, conferring genomic instability and changes in cell cycle regulation, including resistance to anoikis, as well as resistance to chemotherapeutic agents ( including doxorubicin).…”
Section: How Nsaids May Influence Cancer Recurrencementioning
confidence: 99%